To solve the equation (-9/8) x - 7 = -25, we can follow the steps below:
1. Distribute (-9/8) to both terms inside the parentheses:
(-9/8) x - 7 = -25
(9/8)x + (9/8)(-7) = -25
2. Simplify:
(9/8)x - 63/8 = -25
3. Add 63/8 to both sides of the equation to isolate (9/8)x:
(9/8)x - 63/8 + 63/8 = -25 + 63/8
(9/8)x = 23/8
4. Multiply both sides of the equation by the reciprocal of (9/8), which is (8/9), to solve for x:
((8/9)(9/8))x = (23/8)(8/9)
x = 23/8 * 8/9
x = 23/9
Therefore, the solution to the equation (-9/8) x - 7 = -25 is x = 23/9.
(-9/8) x - 7 =-25
1 answer